Modulation of neural activity and gene expression by arecoline - Li, Xiaonan; Gao, Jie; Liu, Xiaomin; Guo, Jianfeng; Liu, Yifan; Cui, Peicai; Yan, Dawei; Fei, Ting; Chen, Ming; Gao, Yihan (Frontiers in Integrative Neuroscience, 2025)
Arecoline, a biologically active alkaloid extracted from the areca nut, serves as the primary psychoactive ingredient in betel quid, one of the most widely consumed psychoactive substances worldwide. Despite its extensive use, the central nervous system (CNS) effects of arecoline remain inadequately understood. This study aims to investigate the central actions of arecoline through a comprehensive, multi-dimensional approach that integrates behavioral assays, neuroimaging techniques, calcium signaling analysis, and transcriptomic profiling. Our findings demonstrate dose-dependent addictive properties of arecoline, alongside distinct behavioral alterations that highlight its potential for addiction. Neuroimaging and calcium signaling data revealed region-specific alterations in neural activity, particularly in areas associated with learning, memory, and reward processing. Furthermore, transcriptomic analysis identified significant changes in gene expression, particularly in pathways related to synaptic plasticity, calcium signaling, and metal ion transport. These results provide valuable insights into the addictive potential of arecoline and its underlying neurobiological mechanisms, offering crucial information for understanding its broader impact on CNS function. The study’s findings hold significant implications for informing public health strategies aimed at addressing arecoline misuse and its potential role in addiction-related disorders.